Topology optimization for a station class surge arrester model. (17th June 2022) - Zhang, Dudu; Kasolis, Fotios; Clemens, Markus
Abstract: High‐voltage stress can cause partial discharges, which in turn result in deterioration of high‐voltage equipment, and hence, in increased maintenance costs. To this end, corona rings are used as means to capacitive field‐grading. In this work, topology optimization is employed for designing alternative layouts for capacitive field‐grading in a station class surge arrester. The objective of the formulated optimization problem is to homogenize the electric field strength along the axis of symmetry of the considered surge arrester. The resulting layout exhibits an improved electric field strength homogeneity profile, when compared to the standard IEC60099‐4:2004 design.